Next-decade needs for 3-D ionosphere imaging - Aa, Ercha; Forsythe, Victoriya V.; Zhang, Shun-Rong; Wang, Wenbin; Coster, Anthea J. (Frontiers in Astronomy and Space Sciences, 2023)
Accurately imaging the 3-D ionospheric variation and its temporal evolution has always been a challenging task for the space weather community. Recent decades have witnessed tremendous steps forward in implementing ionospheric imaging, with the rapid growth of ionospheric data availability from multiple ground-based and space-borne sources. 3-D ionospheric imaging can yield altitude-resolved electron density and total electron content (TEC) distribution in the target region. It offers an essential tool for better specification and understanding of ionospheric dynamical variations, as well as for space weather applications to support government and industry preparedness and mitigation of extreme space weather impact. To better meet the above goals within the next decade, this perspective paper recommends continuous investment across agencies and joint studies through the community, in support of advancing 3-D ionospheric imaging approach with finer resolution and precision, better error covariance specification and uncertainty quantification, improved ionospheric driver estimation, support space weather nowcast and forecast, and sustained effort to increase global data coverage.